2003
DOI: 10.1071/ch02245
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Isotope and Collision Energy Effects in the Dissociation of Chloride and Bromide Adducts of Aliphatic Alcohols, Benzaldehyde, and 2,4-Pentanedione

Abstract: A tandem-in-space triple quadrupole mass spectrometer was used to measure kinetic isotopic effects (KIEs) for the dissociation of chloride and bromide adducts of several compounds that bind halide anions via either hydrogen bonds or by nucleophilic attachment. Two isotopomers of each adduct were simultaneously mass-selected in the first quadrupole and dissociated by collision with argon in the second quadrupole. The KIEs were measured by comparing the extents of dissociation of the lighter versus the heavier i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…A comparison of the present value with KIEs reported for β-H eliminations of deuterated transition-metal complexes is complicated by the fact that the latter almost completely refer to inter molecular assays. Intra- and intermolecular KIEs are not necessarily equivalent, however …”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the present value with KIEs reported for β-H eliminations of deuterated transition-metal complexes is complicated by the fact that the latter almost completely refer to inter molecular assays. Intra- and intermolecular KIEs are not necessarily equivalent, however …”
Section: Discussionmentioning
confidence: 99%
“…The data in the figure suggests that CH 3 OH possesses a higher fluoride affinity than its isotopologue CD 3 OH, a result that corresponds to a normal secondary kinetic isotope effect (KIE). 18,[60][61][62][63][64] A value for the KIE of 1.3 was calculated from the ratio of the abundances of the product ions ([CH 3 OH + F] -/ [CD 3 OH + F] -). Based on this result and supposing an effective temperature of 437 K for the dissociation of such fluoride dimer, the fluoride affinity of CD 3 OH was calculated and found to be 94.5 kJ mol -1 .…”
Section: Kinetic Isotope Effectsmentioning
confidence: 99%
“…Extremely large Cl-KIEs of CHCl4 − during CID were observed and inferred to be owing to the near-threshold centrifugal effect [14], while Petersen et al concluded the Cl-KIEs were caused by symmetry-induced degeneracy of vibrational modes [19]. Augusti et al observed large normal and inverse Cl-KIEs of chloride adducts of aliphatic alcohols, benzaldehyde, and 2,4-pentanedione during CID [16], and deduced that the Cl-KIEs were triggered by differences of zero-point energies (∆ZPEs) between isotopomers, which was in agreement with the conclusions of Gozzo et al [15]. However, Lehman et al indicated that KIEs in CID could not ascribe to ∆ZPEs based on the observed KIEs of diatomic ions [20].…”
Section: Introductionmentioning
confidence: 99%
“…By means of MS, KIEs can be readily determined and applied to probing reaction mechanisms of molecules and ions in gaseous phase [8][9][10]. So far, most studies relevant to on-MS KIEs focused on hydrogen/deuterium (H/D) KIEs [5,[11][12][13], whereas a few concerned heavy-atom KIEs such as chlorine KIEs (Cl-KIEs) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation